Investment Activities of European Venture Capital Funds and the Influences of Fund Providers on their Specialization Patterns - Yiallourou, Christina (2006)
The existing literature suggests that the specialization patterns of venture capital (VC) funds and their finance providers is an interesting aspect of the venture investment process. It is often asserted that the specialization patterns regarding their investments differ considerably according to their preferred stage of enterprises, development or industry sector indicating the heterogeneity in the way they are organized. However, there is little empirical research on the identification of the specific investments choices of VC firms and on the relation between their investment activities and their sources of finance.